2018
DOI: 10.1007/s00604-018-2673-1
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence polarization gene assay for HIV-DNA based on the use of dendrite-modified gold nanoparticles acting as signal amplifiers

Abstract: The authors describe a fluorescence polarization assay for HIV-DNA. It is based on the use of gold nanoparticles (AuNPs) modified with DNA dendritic macromolecules that act as signal amplifiers. In the presence of HIV-DNA, the AuNP-DNA dendritic macromolecules and fluorescently labeled DNA probe combine with HIV-DNA in a sandwich format to form a conjugate. This reaction slows down the rotational speed of the labeled DNA probe because of the increase of molecular weight and volume. This increases fluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…As a result, the rotation speed of the labeled DNA probe slowed down, causing an increase in fluorescence polarization and system sensitivity. Experimental results showed that HIV-DNA could be detected in concentrations as low as 73 pM, and that when HIV-DNA concentrations was within 150 pM to 6 nM, HIV-DNA concentration and FP had a good linear relationship [ 37 ].…”
Section: Nanostructured Fp-based Biosensorsmentioning
confidence: 99%
“…As a result, the rotation speed of the labeled DNA probe slowed down, causing an increase in fluorescence polarization and system sensitivity. Experimental results showed that HIV-DNA could be detected in concentrations as low as 73 pM, and that when HIV-DNA concentrations was within 150 pM to 6 nM, HIV-DNA concentration and FP had a good linear relationship [ 37 ].…”
Section: Nanostructured Fp-based Biosensorsmentioning
confidence: 99%
“…First, 13 nm AuNPs were prepared by sodium citrate reduction according to a previously reported method. Briefly, 2 mL of 1% HAuCl 4 mixed with 49 mL of H 2 O was heated to boiling with continuous stirring. Subsequently, 570 μL of 10% sodium citrate was quickly added under vigorous stirring, and then the solution was continued to boil for 15 min after the color of the solution changed from light yellow to deep red.…”
Section: Experiments Sectionmentioning
confidence: 99%
“…To enhance the diagnosis sensitivity, numerous nanomaterials such as carbon nanotubes [91], AuNPs [92], and Ag nanoparticle [93], etc were utilized to amplify fluorescence polarization signals. Liang and coworkers constructed a fluorescence polarization assay system for diagnosis of HIV-DNA through AuNPs self-assembled by the functional dendritic macromolecules [94]. Firstly, AuNPs loaded by two DNA probes as reporters were prepared.…”
Section: Fluorescence Polarization Assaymentioning
confidence: 99%